KESIAPSIAGAAN DAN PEMETAAN ALIRAN LONGSOR BAHAN ROMBAKAN (DEBRIS FLOW) - I Nengah Sinarta; A.A Gede Sumanjaya; I Made Surya Kumara; I Made Adi Bhaskara; I Made Kusuma Wiranata (Jurnal Abdi Daya, 2024)
Landslide events are natural phenomena where material on a slope adjusts to a new stability state. This process occurs when the load on the slope increases or its inclination becomes steeper, causing the material to slip along a critical failure plane. Such movements involve downward displacement of materials, which may include soil, rock, or artificial fill. Landslide disasters can be triggered by earthquakes or intense rainfall. On October 18, 2021, a magnitude 4.8 earthquake struck near Karangasem, Bali, at a depth of 10 km, leading to landslides that resulted in 2 fatalities and damage to 171 buildings in Bangli Regency. Areas at risk of landslides, such as Dusun Dukuh, require a disaster mitigation scheme to minimize losses in life and property. Currently, the disaster response team in Dusun Dukuh is underactive in public awareness and lacks understanding of maintaining the donated early warning system. The proposed solution involves strengthening the disaster response team through mapping debris flow-prone areas and improving evacuation methods and hazard recognition. The methodology includes two primary activities: identifying and mapping vulnerable settlements and conducting outreach and training on landslide signs and evacuation procedures. The findings highlight the need for comprehensive risk mapping and the development of a robust local volunteer network. Enhancing the disaster response team's capacity through modern technology and improved infrastructure has proven effective in increasing preparedness for debris flow events. With appropriate implementation strategies, risk mitigation in Dusun Dukuh can be more effective and responsive to future disaster threats